A ratiometric fluorescent hydrogen peroxide chemosensor manipulated by an ICT-activated FRET mechanism and its bioimaging application in living cells and zebrafish. Issue 15 (11th July 2018) - Xu, Kaixin; He, Longwei; Yang, Xueling; Yang, Yunzhen; Lin, Weiying
Abstract : A ratiometric fluorescent chemosensor manipulated by an ICT-activated FRET mechanism was engineered for monitoring hydrogen peroxide in living cells and zebrafish. Abstract : A H2 O2 -responsive fluorescent chemosensor (CNBE) with a ratiometric emission signal was elaborately designed and synthesized. The ratio signal of the chemosensor was manipulated by an interplaying ICT-activated FRET mechanism. The ratiometric fluorescence imaging was successfully applied to detect H2 O2 using CNBE in living cells and zebrafish.